Asian parenting, parental control and adolescent's reactive/proactive aggression : effortful control as a moderator - Chua, Michelle Hui Xuan (2011)
This study investigated the relations between temperamental effortful control and parenting (maternal guan, psychological control, and behavioral control) on reactive and proactive aggression in a community sample of 1049 Singapore adolescents (12-17 years). Additionally, we examined interactions between effortful control and psychological control in predicting aggression. Hierarchical regression analyses showed that (a) reactive aggression was positively associated with maternal guan and psychological control, and negatively related to effortful control, and (b) proactive aggression was positively associated with maternal psychological control, and negatively related to behavioral control and effortful control. No significant Effortful Control x Psychological Control interaction was found. Findings point to the influence of parenting and temperament on aggression in an Asian context. Implications for parenting interventions are discussed.